EFFECT OF ADDING Saccharomyces cerevisiae AS PREBIOTIC TO JAPANESE QUAIL DIET ON PRODUCTION PERFORMANCE AND SOME BLOOD PARAMETERS - JASSIM, MAHDI S.; SHANOON , AMMAR KH.; Taha, Mustaffa M.; Ali, Muhanad A. (Diyala Agricultural Sciences Journal, 2013)
This study was conducted in Animal Dept. Poultry Farm College of Agriculture to determine the effect of Saccharomyces cerevisiae yeast on performance and some blood parameters of Japanese Quail by using 48 birds. The birds were randomly distribution on four treatments(12birds)each treat 3replicat, the treatments were T1 using diet without any add (control),T1 ,T3 ,T4 added of S. cerevisiae 5, 10, 15gm per kg diet respectively. The results showed that there are no significant effects on feed consumption and feed conversion while eggs weight and H.H production were increase in T2, T2, T3, T4 treatments compared with control group. No significantly differences recorded between treatments in egg quality characteristics. There is significant decrease in cholesterol, significant increase glucose, no significantly difference in uric acid of serum blood for all experiment treatments compared with control. There is significant effect on carcass weights and carcass mains parts for all experiment treatment compared with control